2007
DOI: 10.1523/jneurosci.3745-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of Motor Responses by Incentive Values through the Basal Ganglia

Abstract: The striatum is a key neural interface for cognitive and motor information processing in which associations between reward value and visual stimulus can be used to modify motor commands. It can guide action-selection processes that occur farther downstream in the basal ganglia (BG) circuit, by encoding the reward value of an action. Here, we report on the study of simultaneously recorded neurons in the dorsal striatum (input stage of the BG) and the internal pallidum (output stage of the BG) in two monkeys per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 28 publications
13
110
0
Order By: Relevance
“…We found significant levels of action value signals before animal's choice of action, which is consistent with previous reports on the monkey DS (Samejima et al, 2005;Lau and Glimcher, 2008; also see Pasquereau et al, 2007). Collectively, our results are most consistent with the possibility that the striatum contributes to action selection only indirectly by conveying values associated potential choices and actual action selection takes place elsewhere.…”
Section: Role Of Striatum In Action Selectionsupporting
confidence: 92%
“…We found significant levels of action value signals before animal's choice of action, which is consistent with previous reports on the monkey DS (Samejima et al, 2005;Lau and Glimcher, 2008; also see Pasquereau et al, 2007). Collectively, our results are most consistent with the possibility that the striatum contributes to action selection only indirectly by conveying values associated potential choices and actual action selection takes place elsewhere.…”
Section: Role Of Striatum In Action Selectionsupporting
confidence: 92%
“…This type of information could easily be conveyed to the context-dependent basal ganglia output neurons that we observed to encode information about the relationship between movement and either successful completion or reward. This finding has been further supported in a recent study of putamen and GPi neurons (Pasquereau et al, 2007). Pasquereau and colleagues demonstrated that the basal ganglia output neurons play a role in both encoding information about the context in which a movement is made, but also appear to execute a computation that can be used to assist the selection of a specific action.…”
Section: Possible Factors That May Influence Context-dependent Dischargementioning
confidence: 69%
“…In sum, the expected value of engaging different neuronal populations, dedicated to specific tasks, might be topographically represented in frontostriatal circuits. In primate prefrontal cortex or striatum, certain neuronal activities have been reported to express both expected reward and various task dimensions, such as target location (Watanabe, 1996;Leon and Shadlen, 1999;Kobayashi et al, 2006) or movement direction (Lauwereyns et al, 2002;Matsumoto et al, 2003;Samejima et al, 2005;Pasquereau et al, 2007). However, the topographical organization of neuronal populations encoding expected values, and their connection with the corresponding effectors, remain to be established.…”
Section: Discussionmentioning
confidence: 99%